Is the Relationship between Exchange Rates and Islamic Indices in Indonesia and Malaysia? (An-Nisbah: Jurnal Ekonomi Syariah, 2018)
This study is aimed to analyze the causal relationship between the exchange rates and Islamic indices in Indonesia and Malaysia, and the long-term relationship of the two variables. Indonesia is represented by the value of the rupiah to US dollar and the Jakarta Islamic Index while Malaysia is represented by the exchange rate of the ringgit to US dollar and the FTSE Bursa Malaysia Hijrah Shariah Index. By using the Vector Autoregression (VAR) model, it can be concluded that the relationship between Jakarta Islamic index is a unidirectional relationship, where the Jakarta Islamic Index affects the exchange rate. The relationship between Malaysia Islamic index has a bidirectional relationship, where the exchange rate affects the FTSE Bursa Malaysia ringgit Hijrah Shariah Index and FTSE Bursa Malaysia Hijrah Shariah Index affects the ringgit exchange rate. Through the study is also concluded that the exchange rate with Islamic indices in Indonesia and Malaysia has a long-term relationship. Keywords: Rupiah, Ringgit, Jakarta Islamic Index, the FTSE Bursa Malaysia Hijrah Shariah Index, VECM